Metformin preferentially provides neuroprotection following cardiac ischemia/reperfusion in non-diabetic rats - Juthipong Benjanuwattra (2020)
Copyright © 2020 Elsevier B.V. All rights reserved. Following acute myocardial infarction, re-establishment of coronary perfusion aggravates further injuries in the heart and remote organs including the brain as a consequence of ischemia/reperfusion (I/R) injury. Since pretreatment with metformin attenuated both cardiac and cerebral I/R injury via AMP-activated protein kinase (AMPK) pathways, we hypothesized that metformin given after ischemia mitigates both cardiac and brain pathologies following cardiac I/R. Male Wistar rats were subjected to either cardiac I/R (30 min-ischemia/120 min-reperfusion; n = 30) or sham operation (n = 5). Metformin 200 mg/kg was given intravenously to the cardiac I/R group (n = 10/group), either during ischemia (D-MET) or at the onset of reperfusion (R-MET). Left ventricular ejection fraction (LVEF) and arrhythmia scores were determined. The heart and brain tissues were collected to determine the extent of injury, mitochondrial function, and apoptosis. Additionally, microglial morphology, Alzheimer's proteins, and dendritic spine density were determined in the brain. Cardiac I/R led to not only reduced LVEF, cardiac mitochondrial dysfunction, and arrhythmias, but also brain mitochondrial dysfunction, apoptosis, Alzheimer's protein aggregation, microglial activation, and dendritic spine loss. A single dose of metformin did not alter p-AMPK/AMPK in both organs. In the heart, impaired LVEF, arrhythmias, infarct size expansion, mitochondrial dysfunction, and apoptosis were not alleviated. On the contrary, metformin attenuated brain mitochondrial dysfunction, apoptosis, and Alzheimer's protein levels. Microglial morphology and dendritic spine density were additionally preserved in D-MET group. In conclusion, metformin given during ischemia preferentially provides neuroprotection against brain mitochondrial dysfunction, apoptosis, microglial activation, and dendritic spine loss in an AMPK-independent manner following cardiac I/R injury.